Mill's Principle of Utility: Origins, Proof, and Implications : Revised and Enlarged Edition - Alican, Necip Fikri (Brill, 2022)
Mill's Principle of Utility: Origins, Proof, and Implications is a defense of John Stuart Mill's utilitarianism with a particular emphasis on his proof of the principle of utility. Supplemented by a comprehensive historical background as well as salient philosophical assumptions and implications, its primary contribution is an analysis, interpretation, and defense of the controversial proof, which has yet to attract a scholarly consensus on how it works and whether it succeeds. The overarching aim of the book is the vindication of Mill's reasoning in the proof and the restoration of his reputation as one of the clearest thinkers of his time.
Keywords: Mill, John Stuart, -- 1806-1873.; Mill, John Stuart, -- 1806-1873. -- Utilitarianism.; Mill, John Stuart, -- 1806-1873; Utilitarianism (Mill, John Stuart); Philosophy and religion.; Philosophy, Medieval.; Philosophy.; Philosophy, English -- 19th century.; Utilitarianism.; Philosophie médiévale.; Philosophie.; Philosophie anglaise -- 19e siècle.; Utilitarisme.; philosophy.; utilitarianism.; Philosophy; Philosophy and religion; Philosophy, English; Philosophy, Medieval; Utilitarianism; 1800-1899